2017
DOI: 10.35790/ecl.5.2.2017.18457
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Indeks Massa Tubuh dan Angka Kejadian Akne Vulgaris pada Siswa-siswi di SMA Frater Don Bosco Manado

Abstract: Acne vulgaris is a chronic inflammatory disease of the pilosebasea follicle. Although the cause of acne vulgaris is not known for certain but there are several pathogenesis suspected to have some effects on the occurrence of acne vulgaris, inter alia the increase in sebum production which is controlled by androgen hormones. Stimulation of androgen hormone production is associated with elevated level of insulin-like growth factor-1 (IGF-1). Increased IGF-1 is correlated positively with body mass index (BMI). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 1 publication
1
4
4
1
Order By: Relevance
“…In this research, a p-value of 0.336 was obtained, inferring no association between BMI and acne vulgaris. This is correlated to a research by Kristiani in 2017 which stated no relationship between BMI and acne vulgaris incidence on students at SMA Frater Don Bosco Manado with a p-value of 0,233 [16]. Despite so, the result of this research does not correspond to the result from a research by Deliana, 2019 which reported that there was an association between BMI and acne vulgaris on students at SMA Negeri 7 Medan (p <0.05) [11].…”
Section: Discussioncontrasting
confidence: 59%
“…In this research, a p-value of 0.336 was obtained, inferring no association between BMI and acne vulgaris. This is correlated to a research by Kristiani in 2017 which stated no relationship between BMI and acne vulgaris incidence on students at SMA Frater Don Bosco Manado with a p-value of 0,233 [16]. Despite so, the result of this research does not correspond to the result from a research by Deliana, 2019 which reported that there was an association between BMI and acne vulgaris on students at SMA Negeri 7 Medan (p <0.05) [11].…”
Section: Discussioncontrasting
confidence: 59%
“…Penampilan merupakan salah satu modal terbentuknya kepercayaan diri. Salah satu masalah yang dapat menurunkan kepercayaan diri seseorang adalah jerawat atau sering dikenal dalam ilmu kedokteran sebagai Acne vulgaris, terutama jerawat yang muncul pada area sekitar wajah yang dapat mengganggu penampilan seseorang sehingga menyebabkan beban pikiran tersendiri bagi sebagian orang (1) .…”
Section: Pendahuluanunclassified
“…AV events are caused by chronic inflammation of the polysebaceous follicles. Inflammation of polysebaceous follicles, one of which can be caused by blockage of polysebaceous follicles due to particles from waterproof foundations that stay for a long time (Kabau, 2012). AV can increase anxiety and depression so that AV sufferers will tend to have feelings of isolation from the social environment, personality changes, and changes in selfconfidence (Goman, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Foundations that are waterproof (not easily erased even if exposed to water) will clog the sebum glands longer and cause an increase in the production of the sebum glands. Some waterproof foundations also contain ingredients that are acnegenic or comedogenic so that they will increase the risk of developing AV (Kabau, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation